Pemberdayaan Komunitas Tuli Gresik (Kotugres) Melalui Pelatihan Bisnis Digital - Supriyanto, Supriyanto; Hadi, Hafid Kholidi; Beny, Acep Ovel Novari; Muhimmah, Hitta Alfi; Wiryanto, Wiryanto (Abimanyu : Jornal of Community Engagement, 2024)
The Gresik Deaf Community (Kotugres) is a community of young and productive deaf people who need to receive digital business training to support their economic independence. This training can also be used as a strategy to empower Kotugres from unfavorable conditions such as negative stigma from society, discrimination, neglect and economic and social marginalization. Kotugres' products need to be marketed digitally after manual/offline business processes have stagnated due to changes in people's mindsets which are starting to abandon offline shopping habits and tend to increase interest in online shopping, especially the Covid-19 pandemic situation which has not yet 100% subsided to create a digital business platform increasingly needed and popular with society. The PKM implementation went well, smoothly, participants were enthusiastic in taking part in the activities and were guided in using the market place. The next stage is preparing PKM outputs in the form of scientific publications in national journals or proceedings, publications in online mass media, and videos of activities uploaded on YouTube.